PELANGGARAN HAM PADA PERISTIWA PENYIKSAAN YANG BERUJUNG PADA TERBUNUHNYA DUA WARGA SIPIL DI PAPUA OLEH ANGGOTA TNI - Yulia Puspita Sari (JURNAL ILMIAH HUKUM DAN DINAMIKA MASYARAKAT, 2021)
So far, the results of the decisions at the Military Courts have not been able to bring a sense of justice to victims and the public and are far from human rights standards that exist as courts regulated in International Covenant on Civil and Political Rights and The Committee Against Torture which has been ratified by Indonesia. In this article, the author wants to examine more deeply the practice of human rights violations during the torture incident which led to the killing of two civilians in Papua by members of the indonesian army and also compare the application of due process to similar cases in other countries. The method used in this article is descriptive analytical with a normative juridical approach. Data collection techniques through literature study. The results show that the incidents of torture that led to the killing of two civilians in Papua by indonesian army members who are part of the gross human rights violations which are very regrettable are still occurring. Sadly, this case will later be tried only through military court. This raises concerns for many parties because it is prone to injustice on the part of the victim. For this reason, it is recommended that the indonesian army be able to transfer this legal process to the general court or human rights court so that equality is created between indonesian army members and ordinary citizens in a legal position in accordance with the principles of the rule of law as contained in the Constitution.